Principalship as an empowering leadership process: the experiences of women school heads in Zimbabwe. - Muzvidziwa, Irene (2016)
The paper explores how women principals approached leadership in schools and empowered others to improve educational outcomes. An in-depth qualitative study which falls within the phenontenological-interpretivist paradigm was adopted as the research design. The emphasis was on rich contextual detail and individuals' lived experiences. Interviews were used to generate information from participants. The findings show rich and diverse cultures of creativity in the way participants adopted strategies of negotiating and coaching, which generated the spirit of trust, respect and ownership among teachers, parents and the community. Despite the many challenges, the women primary school principals managed to excel.